Estimation Renalase Concentration in Iraqi Patients with End Stage Renal Disease in Hilla Province - Shammari, Ahmed Abdulhaleem Al (International Journal of Scientific Research in Biological Sciences, 2024)
ESKD is a major contributor to Iraq`s high healthcare costs and a prevalent, debilitating condition that shortens and worsens patients` lives. These individuals often suffer from diabetes and cardiovascular disease, and they have a significant risk of dying from cardiovascular causes. Dialysis or kidney transplantation are the mainstays of renal replacement treatment in ESKD management. We collected 100 blood samples from patients with stage renal illness admitted to Merjan Teaching Hospital in Babylon Province, Iraq. Everyone involved, from the patients to the 100-person control group of healthy adults ranging in age from 11 to 80, belonged to the same Arab ethnic group. Results showed that renalase levels varied by an average of pg/ml in both the experimental and control groups. The serum of individuals with end-stage renal disease had significantly higher renalase levels (184.21± 4.97 pg/ml) compared to the healthy group (44.06±7.21 pg/ml) (P <0.05).conclusion: In this study, we looked at the renalase levels of end-stage renal disease (ESRD) patients who were on hemolysis. These individuals had elevated serum renalase levels. Research shows that renalase production is higher in people with end-stage renal disease (ESRD) and gets worse as the disease progresses. Patients with end-stage renal disease (ESRD) who are undergoing hemolysis are most likely to have elevated serum renalase concentrations due to compensatory synthesis in extrarenal organs caused by hypertension and alterations in the cardiovascular system. It is possible that serum renalase`s enhanced degradation of catecholamines is responsible for the lower plasma concentrations of these substances. This could be proof that renalase is involved in catecholamine metabolism.